Reform of Middle Eastern militaries : lessons from Indonesia - Dorsey, James M. (2014)
The recent commando raid on a prison by Indonesian special forces provoked renewed debate about the need to futther reform the military and subject it to civilian justice - 15 years after the end of autocratic rule in Jakarta. This illustrates the difficult road post-revolt nations in the Middle East and North Africa have to travel.